Chapter 10 'Aid the victims of German fascism!' Transatlantic networks and the rise of anti-Nazism in the USA, 1933-1935 - Braskén, Kasper (Taylor & Francis, 2021)
Anti-fascism became one of the main causes of the American left-liberal milieu during the mid-1930s. The chapter offers a new analysis of two communist-led, international organisations called the World Committee against War and Fascism and the World Relief Committee for the Victims of German Fascism. The chapter aims to show how anti-Nazi activities were initially mobilised in the USA from 1933 to 1935. It reveals the transnational connections present in American anti-fascist movements and shows the importance of the connections established between American anti-fascists and German, British and French anti-fascists before the beginning of the popular front period. It provides new insights to the ways anti-fascist ideas and practices were effectively circulated across the Atlantic and within North America. The time period was filled with contradictions and ambiguities especially due to the Communist International's sectarianism that initially hampered co-operation within the broader American left. Still, transatlantic anti-fascist solidarity networks had already managed by mid-1933 to inspire local anti-Nazi activism across the USA.